Interference Structures in the High-Order Above-Threshold Ionization Spectra of Polyatomic Molecules in a Bicircular Laser Field - Elvedin Hasović; Azra Gazibegović-Busuladžić; Mustafa Busuladžić (Molecules)
We analyze the high-order above-threshold ionization (HATI) process of a small polyatomic molecule with C3 symmetry, which is induced by a bicircular strong laser field. This field consists of two coplanar, counter-rotating, circularly polarized components with frequencies <semantics>rω</semantics> and <semantics>sω</semantics> where r and s are integers. In our study, we use an improved molecular strong-field approximation to obtain electron energy-angle-resolved and momentum spectra of the BF3 molecule. We analyze the contributions of individual atoms as well as the impact of molecular symmetries on these spectra. We find that these spectra are significantly affected by the characteristics of the molecule and the laser-field parameters. Furthermore, we observe pronounced interference minima in the HATI spectra. We demonstrate that these minima result from the destructive interference of rescattered wave packets from different atomic centers, and we determine the conditions under which they occur, including two-, three-, and four-center interference.